MTP: Model Transformation Profile - Mascarenhas, Ana Patrícia Fontes Magalhães; Andrade, Aline Maria Santos; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2013)
Model Driven Development (MDD) is a softwaredevelopment approach that makes intensive use of modelsallowing not only reuse of code but also reuse of models producedalong the entire software development life cycle. At the core ofMDD is a transformation chain that transforms input modelsinto output models until code generation enabling softwaredevelopment automation. However, despite the importance of thedevelopment automation provided by MDD, there is a lack ofmodeling strategies to support transformation specification: theyare usually specified in natural language and implementeddirectly in code. As a result, it is difficult to adopt best practicesof software development and enable reuse. This paper proposes amodel transformation profile (MTP) suitable for thetransformation specification since requirements elicitation.MTP provides specifications independent of platform that can bereused to generate code in different transformation languages.This profile is a specialization of UML to the transformationdomain taking advantage of the large number of tools thatsupports this language widely used by industry and academy.